(untitled) (African Human Mobility Review, 2021)
Since the 2008 attacks on African migrants, xenophobic violence has become a form of social agency for responding to increasing unemployment, destitution and crime in South Africa. Africans living and operating businesses in urban and peri-urban areas are now objects of different forms of social violence, as they are repeatedly blamed for unfulfilled political promises by the ANC-led government. One of most victimised African migrant communities is the Somali community, whose business activities in cities and townships are perceived as undesirable threats to locals’ sources of livelihood. This article uses qualitative data collected from 30 Somali migrants in Bellville and Khayelitsha, Cape Town to examine how Somalis’ co-existence with South Africans and their business tactics in Cape Town intersect to influence xenophobic violence. It explores the relationship between risky entrepreneurship and xenophobia, and the threats that this relationship poses to Somali lives.